Encouraging parents to invest: A randomized trial with two simple interventions in early childhood - Cara Ebert; Esther Luise Heesemann; Sebastian Vollmer (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2020)
The lottery of birth draws some children into deprived environments and others into environments where they thrive. In a field experiment in rural India with 10-20 months old children we test two scalable interventions to reduce early disadvantages in health and mental development. We distribute a durable device for home iron fortification of meals, called the Lucky Iron Leaf, and picture books together with a training for caregivers in dialogic reading. We find no significant average impact of either intervention on anemia or mental development. However, we find a cross-productivity of children's baseline health and the interventions' effectiveness. Children, who are non-anemic at baseline, improve in receptive language skills by half a standard deviation one year after implementation.
Keywords: D04; I12; I15; J13; 330; Early Childhood; Parental Investment; Nutrition; Health Behavior; Human Capital